Bacterial lipopolysaccharides as inducers of disease resistance in tobacco. - Graham, T L (Appl Environ Microbiol, 1977)
The cell wall component of Pseudomonas solanacearum that induces disease resistance in tobacco was highly heat stable at neutral or alkaline pH but highly labile at acid pH. Activity was unaffected by nucleases and proteases but destroyed by a mixture of beta-glycosidases. Washing of bacterial cell walls released a lipopolysaccharide (LPS) fraction with high inducer activity. Purified LPS, extracted by a variety of procedures from whole cells, isolated cell walls, and culture filtrates of both smooth and rough forms of P. solanacearum, induced disease resistance in tobacco at concentrations as low as 50 microgram/ml. The LPS from the non-plant pathogens Escherichia coli B, E. coli K, and Serratia marcescens was also active. Cell wall protein, free phospholipid, and nucleic acids were not necessary for activity. Moreover, since LPS from rough forms was active, the O-specific polysaccharide of the LPS was not required for activity. Hydrolysis of the remaining core-lipid A linkage or deacylation of lipid A destroyed inducer activity. When injected into tobacco leaves, purified LPS attached to tobacco mesophyll cell walls and induced ultrastructural changes in the host cell similar to those induced by attachment of whole heat-killed bacteria. IMAGES: